1976
DOI: 10.1111/j.1445-5994.1976.tb03287.x
|View full text |Cite
|
Sign up to set email alerts
|

Diazoxide‐induced Benin Release in Diagnosis of Remediable Renovascular Hypertension*

Abstract: In hypertensive patients with unilateral renal artery stenosis, intravenous diazoide increased renal vein renin activity more on the involved side than on the contralateral side, whereas, in a group with predominantly unilateral renal parenchymal disease, the increase in renal vein was similar for both kidneys. In patients with bilateral renal artery stenosis, the use of diazoxide was helpful in lateralizing the dominant ischaemic lesion. Diazoide administration appears to be a safe, rapid and convenient metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1978
1978
1984
1984

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Mean values for blood pressure, pulse rate, plasma renin activity, and body weight of 15 patients in the double-blind randomized crossover study < 0.01 activity by radioimmunoassay 14. Statistical analyses were made by Student's paired t test.Blood pressure responses in individual patients were graded by the method of Walker and coworkers 15.…”
mentioning
confidence: 99%
“…Mean values for blood pressure, pulse rate, plasma renin activity, and body weight of 15 patients in the double-blind randomized crossover study < 0.01 activity by radioimmunoassay 14. Statistical analyses were made by Student's paired t test.Blood pressure responses in individual patients were graded by the method of Walker and coworkers 15.…”
mentioning
confidence: 99%
“…Twelve (38 %) of our 32 successfully operated cases were diagnosed preoperatively only when stimulation results were used. Some earlier studies have also shown that additional renin-positive patients are discovered by such stimulation procedures and successfully treated with surgery (8,9,(22)(23)(24)(25). These studies together report on 60 successful cases, 23 (38 %) of whom appear to have been identified only by their renin pattern after stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…In all cases, antihypertensive therapy was withdrawn for one week or longer and then baseline plasma renin activity was determined as previously reported (Stokes et al, 1976). The values obtained were graded as low, normal or high by reference to a nomogram relating 118 determinations of peripheral plasma renin activity (erect posture) to concurrent urinary sodium excretion in 76 normal activity and blood pressure responses to saralasin n.a.…”
mentioning
confidence: 99%